Exploring Students’ Anxiety in Writing Thesis Proposal - Dian, Octa Sinar Anisah; Rahmawati, Wiki Tedi; Prihatini, Syafrina (English Education Study Program FKIP Universitas Alwashliyah Medan, 2024)
This study aims to explore the anxiety experienced by students during the thesis proposal writing process, focusing on the factors that influence the level of anxiety and the strategies used by students to overcome it. This study uses a qualitative approach with a narrative inquiry method to explore students' personal experiences in depth. Data were collected through observation and in-depth interviews with the participants from two final semester students in the English Education Study Program, Al Washliyah University, Medan. The results of the study indicate that the anxiety experienced by students in writing thesis proposals is triggered by various internal and external factors. Although students try various strategies to reduce anxiety, such as dividing tasks into small parts, consulting with lecturers, and using relaxation techniques, anxiety remains a major obstacle in the thesis proposal writing process. This study provides important insights into the importance of more empathetic and systematic guidance, as well as adequate support to improve students' mental well-being during the thesis writing process.